Exploring commercial environmental factors affecting the adoption of mobile payment - Manoharan, Sharmila; Ab Rahman, Rozanah; Abu Bakar, Elistina (Pennwell Corporation, 2020)
The advancement in mobile technology helps the massive growth of mobile users across the globe. The expansion of advanced mobile technologies and improved mobile devices resulted in the emergence of mobile payment (M-payment) technologies. Despite the facilitative business environment, M-payment penetration among the developing countries is still low compared to traditional financial instruments such as bank transfer, cash in circulation, and credit cards. Presently, there are multiple literature on adopting M-payment from a consumer’s perspective, but not from the supplier’s perspective. This study critically analysed the existing literature and proposed a framework based on the contingency theory (CT) and the technology adoption model (TAM) as a technology penetration framework to explore the M-payment service providers (MPSP) role on the adoption of M-payment. Technology adoption is greatly facilitated by environmental factors and technology attributes that influence it. Furthermore, this study proposed a conceptual framework to explore M-payment adoption by including the MPSP perspective and exploring the commercial environmental factors, technology attributes of perceived usefulness, perceived ease of use, trust, and risk influencing M-payments penetration and influence on the M-payment adoption. The conceptual framework in this paper also offers valuable insights from the MPSP, industry regulators, and mobile technology experts.